William Forsythe's Postdramatic Dance Theater Unsettling Perception - Vass, Freya (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book takes choreographer William Forsythe's choreographic and scenographic processes as a holistic lens through which to view dance as a fundamentally visuo-sonic art form and choreography as a form of perceptual experimentation. In doing so, it reveals how the made worlds within which postdramatic dance is situated influence how choreography is perceived. Resonating with ecological perspectives but also drawing on an extensive range of cognitive research approaches, the volume's choreo-scenographic perspective emphasizes the importance of considering the expanded scenography of lighting, sound, space, scenic elements, costume, and performer movement when analyzing the sensory and cognitive perception of dance. The volume provides a first book-length cognitive study of both an individual choreographer and the aesthetics of postdramatic theatre. It also satisfies a need for more dedicated scholarship on Forsythe, whose extensive and varied array of groundbreaking ballets and dance theater works for the Ballett Frankfurt (1984-2004), The Forsythe Company (2005-15), and as an independent choreographer have made him a key figure in 20th/21st century dance. Freya Vass is a Lecturer in Drama and Theatre at the University of Kent, UK, and a freelance dance dramaturg. Her principal research interests include cognitive dance studies, dance dramaturgy, performativity, devising, and arts-sciences interdisciplinarity. A former professional dancer with companies in Europe and the US, she holds a PhD in Dance History and Theory and was Dramaturg and Production Assistant for The Forsythe Company from 2006 - 2013. .
Keywords: Performing arts; Theater; Dance; Actors; Theater -- History; Theatre and Performance Arts; Dance; Performers and Practitioners; Contemporary Theatre and Performance